Diagnoses Treated in Ambulatory Care Among Homeless-Experienced Veterans: Does Supported Housing Matter?. (October 2016) - Gabrielian, Sonya; Yuan, Anita H.; Andersen, Ronald M.; Gelberg, Lillian
Purpose: Little is known about how permanent supported housing influences ambulatory care received by homeless persons. To fill this gap, we compared diagnoses treated in VA Greater Los Angeles (VAGLA) ambulatory care between Veterans who are formerly homeless—now housed/case managed through VA Supported Housing ("VASH Veterans")—and currently homeless.Methods: We performed secondary database analyses of homeless-experienced Veterans (n = 3631) with VAGLA ambulatory care use from October 1, 2010 to September 30, 2011. We compared diagnoses treated—adjusting for demographics and need characteristics in regression analyses—between VASH Veterans (n = 1904) and currently homeless Veterans (n = 1727).Results: On average, considering 26 studied diagnoses, VASH (vs currently homeless) Veterans received care for more ( P < .05) diagnoses (mean = 2.9/1.7). Adjusting for demographics and need characteristics, VASH Veterans were more likely ( P < .05) than currently homeless Veterans to receive treatment for diagnoses across categories: chronic physical illness, acute physical illness, mental illness, and substance use disorders. Specifically, VASH Veterans had 2.5, 1.7, 2.1, and 1.8 times greater odds of receiving treatment for at least 2 condition in these categories, respectively. Among participants treated for chronic illnesses, adjusting for predisposing and need characteristics, VASH (vs currently homeless) Veterans were 9%, 8%, and 11% more likely to have 2 or more visits for chronic physical illnesses, mental illnesses, and substance use disorder, respectively.Conclusion: Among homeless-experienced Veterans, permanent supported housing may reduce disparities in the treatment of diagnoses commonly seen in ambulatory care.